Patients and Their Companion Perception about Disease and How to Communicate to Medical Practitioners - Ganiem, Leila Mona; Komalawati, Euis; Pandjaitan, Rosmawati Hilderiah; Hani, Rafika (Jurnal Komunikasi, 2022)
Understanding the patient's and companion's perception of the patient's illness can improve the patient's compliance and overall satisfaction. Patients' understanding of their illness is essential for recovery. Doctors should understand the perceptions and interpretations about the illness, experience, knowledge and culture of patients and their companions. The disease is what happens to the patient. Arthur Kleinman's Explanatory Model of Illness provides a guide for understanding the patient's point of view. The purpose of this study was to explore the meaning of stroke experienced by patients, according to the point of view of the patient and his companion, and the treatment they had, second, to explore how the patient and the companion convey the condition to the doctor. The method uses a phenomenological approach through interviews, observations, and secondary patient data. There are two primary informants, namely two patients and two companions. This study's results indicate a gap regarding the meaning of the disease between the patient's conception and the health sciences. Patients' and their companion's perceptions denote the economic, social, and political background in terms of the patient's illness. The information that patient and companion convey to doctors, usually do not whole information about what they have done during the journey of treatment. Models for interaction that are mainly developed are between doctor and patient. For effective communication between doctor and companion to help the patient better, there is an important model for consultation that includes triadic communication: doctor-patient-companion which can be advantageous. Important also for the doctor to upgrade the knowledge about understanding not only biomedical information but also the socio, psycho, cultural, and religion of the patient.